PENGEMBANGAN MODUL PEMBELAJARAN KONTEKSTUAL BERBASIS MULTIPLE REPRESENTATIONS PADA MATERI FLUIDA STATIS - Radha Indah Pratiwi; I Dewa Putu Nyeneng; Ismu Wahyudi (Jurnal Pembelajaran Fisika, 2017)
This study aims to produce a contextual learning module based on multiple representations on the static fluid topic that is validated, attractive, easy, useful and effective. This research uses research and development research method with One-Group Pretest-Posttest research design. Furthermore, the expert test of the product consisting of expert test design and expert test of the topic with good result and the product is stated